Cancer Stem Cell Immunology: Key to Understanding Tumorigenesis and Tumor Immune Escape? - Bruttel, Valentin S.; Wischhusen, Jörg (Frontiers in Immunology, 2014)
Cancer stem cell (CSC) biology and tumor immunology have shaped our understanding of tumorigenesis. However, we still do not fully understand why tumors can be contained but not eliminated by the immune system and whether rare CSCs are required for tumor propagation. Long latency or recurrence periods have been described for most tumors. Conceptually, this requires a subset of malignant cells which is capable of initiating tumors, but is neither eliminated by immune cells nor able to grow straight into overt tumors. These criteria would be fulfilled by CSCs. Stem cells are pluripotent, immune-privileged and long-living, but depend on specialized niches. Thus, latent tumors may be maintained by a niche-constrained reservoir of long-living CSCs that are exempt from immunosurveillance while niche-independent and more immunogenic daughter cells are constantly eliminated. The small subpopulation of CSCs is often held responsible for tumor initiation, metastasis and recurrence. Experimentally, this hypothesis was supported by the observation that only this subset can propagate tumors in NOD/scid mice which lack T and B cells. Yet, the concept was challenged when an unexpectedly large proportion of melanoma cells were found to be capable of seeding complex tumors in mice which further lack NK cells. Moreover, the link between stem cell-like properties and tumorigenicity was not sustained in these highly immunodeficient animals. In humans, however, tumor propagating cells must also escape from immune-mediated destruction. The ability to persist and to initiate neoplastic growth in the presence of immunosurveillance could hence be a decisive criterion for CSCs - which would be lost in a maximally immunodeficient animal model. Consequently, integrating scientific insight from stem cell biology and tumor immunology to build a new concept of “cancer stem cell immunology” may help to reconcile the outlined contradictions and to improve our understanding of tumorigenesis.